2020
DOI: 10.1029/2019je006240
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Infrared Microspectroscopy of Experimentally Shocked Basalts

Abstract: Petrographic, micro‐Raman and micro‐Fourier transform infrared spectral analyses of experimentally shocked basalt and basaltic andesite samples (up to ~63 GPa) indicated that progressive amorphization of plagioclase feldspar with increasing pressure resulted in detectable spectral variations that mimic those of the experimentally shocked, plagioclase‐dominated rocks analyzed in earlier studies. However, variations in starting sample composition and/or shock propagation through the minerals and mesostasis withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
(182 reference statements)
1
4
0
Order By: Relevance
“…This relationship between grain size and amorphization pressure in plagioclase has been demonstrated experimentally (Johnson et al. 2020).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This relationship between grain size and amorphization pressure in plagioclase has been demonstrated experimentally (Johnson et al. 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Complete amorphization of plagioclase in NWA 032 and partial amorphization in paired meteorites may be reconciled by the fine-grained nature of NWA 032 groundmass, where conversion to glass is facilitated by fine grain sizes owing to the shorter length scale of dislocations. This relationship between grain size and amorphization pressure in plagioclase has been demonstrated experimentally (Johnson et al 2020).…”
Section: Revised Shock Conditions For Nwa 032 and Paired Basaltic Metmentioning
confidence: 60%
“…Micro-FTIR (Fourier Transform Infrared Spectroscopy) is a powerful tool for investigating planetary materials (Jaret, Johnson, et al, 2018;Johnson et al, 2020;Kereszturi et al, 2015Kereszturi et al, , 2017Kereszturi et al, , 2023Morlok et al, 2010Morlok et al, , 2012Morlok et al, , 2019Morlok et al, , 2020Zeng et al, 2019). Previous studies have shown that the micro-FTIR spectra are sensitive to the structure of plagioclase, including unshocked plagioclase, partially shocked plagioclase, and high-pressure maskelynite Jaret et al, 2015;Martin et al, 2017;Zeng, Joy, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mid‐infrared (MIR) spectroscopy has been used to great success toward quantitatively determining the mineralogy of geologic samples (Clark & Roush, 1984; Hapke, 1981; Hunt & Salisbury, 1970; Johnson et al., 1983; King & Ridley, 1987; Mustard & Pieters, 1987). It has been employed in a variety of contexts from determining bulk composition of powdered samples (Friedlander et al., 2015; Lane et al., 2011; Shirley & Glotch, 2019) to spectroscopic imaging of rock sections via micro‐Fourier transform infrared (micro‐FTIR) (Farrand et al., 2016, 2018; Jaret et al., 2015, 2018; Johnson et al., 2020; Yesiltas et al., 2019; Yesiltas & Kebukawa, 2016).…”
Section: Introductionmentioning
confidence: 99%